Community-based house improvement for malaria control in southern Malawi: Stakeholder perceptions, experiences, and acceptability - Tinashe A. Tizifa; Steven Gowelo; Alinune N. Kabaghe; Robert S. McCann; Tumaini Malenga; Richard M. Nkhata; Asante Kadama; Yankho Chapeta; Willem Takken; Kamija S. Phiri; Michele van Vugt; Henk van den Berg; et al. (Public Library of Science (PLoS), 2022)
House improvement (HI) refers to the full screening or closing of openings such as windows, doors, and eaves, as well as the installation of ceilings, to reduce mosquito-human contact indoors. HI is a viable supplementary intervention that reduces malaria transmission further than the existing strategies alone. In Malawi, HI has not been widely implemented and evaluated for malaria control. Concerns about lack of local evidence, durability in different epidemiological and cultural settings, and the cost of large-scale implementation are among the reasons the strategy is not utilised in many low-income countries. This study assessed community perceptions, experiences, and acceptability of community-led HI in Chikwawa district, southern Malawi. This was a qualitative study where separate focus group discussions were conducted with members from the general community (n = 3); health animators (n = 3); and HI committee members (n = 3). In-depth interviews were conducted with community members (n = 20), and key-informant interviews were conducted with health surveillance assistants and chiefs (n = 23). All interviews were transcribed and coded before performing a thematic content analysis to identify the main themes. Coded data were analysed using Nvivo 12 Plus software. Study participants had a thorough understanding of HI. Participants expressed satisfaction with HI, and they reported enabling factors to HI acceptability, such as the reduction in malaria cases in their villages and the safety and effectiveness of HI use. Participants also reported barriers to effective HI implementation, such as the unavailability and inaccessibility of some HI materials, as well as excessive heat and darkness in HI houses compared to non-HI houses. Participants indicated that they were willing to sustain the intervention but expressed the need for strategies to address barriers to ensure the effectiveness of HI. Our results showed the high knowledge and acceptability of HI by participants in the study area. Intensive and continued health education and community engagement on the significance of HI could help overcome the barriers and improve the acceptability and sustainability of the intervention.